Purifying the land of the pure : a history of Pakistan's religious minorities - Ispahani, Farahnaz (Oxford University Press, 2017)
In Purifying the Land of the Pure, Farahnaz Ispahani analyzes Pakistan's policies towards its religious minority populations, both Muslim and non-Muslim, since independence in 1947.